Prospective Study on Prophylactic Micafungin Sodium against Invasive Fungal Disease during Neutropenia in Pediatric & Adolescent Patients Undergoing Autologous Hematopoietic Stem Cell Transplantation - Bo-Kyung Kim; Jung-Yoon Choi; Kyung-Taek Hong; Hong-Yul An; Hee-Young Shin; Hyoung-Jin Kang (MDPI AG, 2022)
Background: Invasive fungal diseases (IFDs) increase the mortality rate of patients with neutropenia who receive chemotherapy or have previously undergone hematopoietic stem cell transplantation (HSCT). Micafungin is a broad-spectrum echinocandin with minimal toxicity and low drug interactions. We therefore investigated the efficacy and safety of prophylactic micafungin in pediatric and adolescent patients who underwent autologous HSCT. Methods: This was a phase II, prospective, single-center, open-label, and single-arm study. From November 2011 to February 2017, 125 patients were screened from Seoul National University Children's Hospital, Korea, and 112 were enrolled. Micafungin was administered intravenously at a dose of 1 mg/kg/day (maximum 50 mg/day) from day 8 of autologous HSCT until neutrophil engraftment. Treatment success was defined as the absence of proven, probable, or possible IFD up to 4 weeks after therapy. Results: The study protocol was achieved without premature interruption in 110 patients (98.2%). The reasons interrupting micafungin treatment included early death (n = 1) and patient refusal (n = 1). Treatment success was achieved in 109 patients (99.1%). Only one patient was diagnosed with probable IFD. No patients were diagnosed with possible or proven IFD. In the full analysis set, 21 patients (18.8%) experienced 22 adverse events (AEs); however, all AEs were classified as "unlikely" related to micafungin. No patient experienced grade IV AEs nor discontinued treatment, and none of the deaths were related to micafungin. Conclusions: Our study demonstrated that micafungin is a safe and effective option for antifungal prophylaxis in pediatric patients who underwent autologous HSCT, with promising efficacy without significant AEs.